A meta-analysis on the effect of expertise on eye movements during music reading - Joris Perra; Alice Latimier; Bénédicte Poulin-Charronnat; Thierry Baccino; Véronique Drai-Zerbib (Bern Open Publishing, 2022)
The current meta-analysis was conducted on 12 studies comparing the eye movements of expert versus non-expert musicians and attempted to determine which eye movement measures are expertise dependent during music reading. The total dataset of 61 comparisons was divided into four subsets, each concerning one eye-movement variable (i.e., fixation duration, number of fixations, saccade amplitude, and gaze duration). We used a variance estimation method to aggregate the effect sizes. The results support the robust finding of reduced fixation duration in expert musicians (Subset 1, g = -0.72). Due to low statistical power because of limited effect sizes, the results on the number of fixations, saccade amplitude, and gaze duration were not reliable. We conducted meta-regression analyses to determine potential moderators of the effect of expertise on eye movements (i.e., definition of experimental groups, type of musical task performed, type of musical material used or tempo control). Moderator analyses did not yield any reliable results. The need for consistency in the experimental methodology is discussed. *The first two authors equally contributed to the first authorship